Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.